(untitled) - Zumdahl, Steven S. (Lexington, Mass, 1995)
Contents: Chemists and chemistry; atoms, molecules, and ions; gases; chemical equilibrium; acids and base; electrochemistry; chemical bonding; biochemistry.
Keywords: Chemistry